International discussion (round table) «Arctic Subsoil and International Law» held at the MGIMO-University MFA Russia - E. F. Pushkareva; A. Yu. Skuratova (Московский журнал международного права, 2008)
Lawyers, economists, diplomats from Russia, Canada, Norway, USA, and Denmark participated in the discussion on the topic. In his opening remarks Professor A N Vylegjanin (Head, Department of International Law, MGIMO) underlined the importance of the topic because of the political and economic value of the statute of arctic subsoil and international law Professor S A Gureev and Dr I Bunik provided a general overview of alternative approaches on defining the statute of arctic high-altitude subsoil. According to them, there is no sense to allow more than 150 states to access the Arctic subsoil, which would happen if the International Area is established in the Arctic Accordingly, they offered alternative principles of delimiting the Arctic Oceans’s subsoil between the arctic states only Professor O Sanders, Director of Canadian Institute of Resources Law, was the main reporter. His report highlighted the following: at the moment, the statute of the Arctic’s high altitude subsoil is of no practical meaning, butit may change in the future; sectoral borders in the Arctic are drawn as state borders on some official Canadian maps, meeting each other at the North Pole; Canadian legislation on the Arctic sector is the oldest (since 1906); Canada, however, is flexible in its implementation.There were differing opinions on some of the issues. The idea of the Arctic states having to transfer part of their continental shelf in the Arctic to the Area was debated; some participants suggested that states are not obliged to do so Furthermore, it is impossible legally: one of the Arctic states is not a member of the 1982 Convention/ The suggestion that Russia has started already establishing the Area in the Arctic by making a submission according to article 76 of the 1982 Convention was criticized, as it is not possible to establish the Area from the Russian side only There was only one question where all participants agreed: rights of a state on its continental shelf exist ipso facto and ab initio and do not depend on any recommendation, including that of the Commission on the Limits of the Continental Shelf/